KRITIK ATAS ISLAMISASI ILMU PENGETAHUAN PERSPEKTIF FAZLUR RAHMAN DAN ZIAUDDIN SARDAR - Walkaromah, Naylul 'Izzah (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Islamization of science is an idea initiated by Naquib al-Attas and Ismail al-Faruqi. Western domination is very strong and Islam is an inferior civilization before the West, so that the Islamization of science becomes the main agenda, especially for Muslims to rise from this downturn. But in fact, this agenda is not necessarily agreed upon by all groups. This agenda caused controversy and criticism by other scholars. Among the intellectuals who criticized this agenda were Fazlur Rahman and Ziauddin Sardar. This type of research is qualitative, and the search for data sources through literature studies. This paper will describe the views and criticisms of the concept of Islamization of science from the perspectives of Fazlur Rahman and Ziauddin Sardar. The conclusion obtained is that according to Fazlur Rahman, science does not have to be Islamized because there is actually nothing wrong in it. Errors are only related to the moral responsibility of users and managers, so there is no need to bother to agenda Islamic science. While in Ziauddin Sardar's perspective, he criticized al-Faruqi's idea of Islamization of science. According to him, Islamizing science based on Islamic teachings in disciplines that have been constructed with Western ideologies and paradigms actually leads to the westernization of Islam and does not include the Islamization of science.